2015
DOI: 10.1128/jvi.00948-15
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus nsp10/nsp16 Methyltransferase Can Be Targeted by nsp10-Derived Peptide In Vitro and In Vivo To Reduce Replication and Pathogenesis

Abstract: The 5= cap structures of eukaryotic mRNAs are important for RNA stability and protein translation. T he 5= ends of eukaryotic cellular mRNAs and most viral mRNAs possess a cap structure, which plays important roles in mRNA splicing, intracellular RNA transport, RNA stability, and translation initiation (1). Host and viral RNA molecules lacking the 5= cap structure are rapidly degraded in the cytoplasm (2). The cap-0 structure of mRNA is cotranscriptionally formed through sequential enzymatic reactions, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
272
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 163 publications
(281 citation statements)
references
References 45 publications
8
272
0
1
Order By: Relevance
“…It has been shown that a natural recombinant strain containing partial nsp regions from a low pathogenic H120 strain in the frame of a nephropathogenic strain possesses attenuated pathogenicity, which suggests strong associations between nsps and IBV virulence39. Studies on other coronaviruses such as MHV and severe acute respiratory syndrome coronavirus (SARS-CoV) have also shown that nsps are associated with viral replication and evasion of host innate immune response via viral RNA modification4041, host mRNA degradation, and IFN antagonist competition42. Therefore, given the low sequence homology in the accessory proteins 3a, 3b, and 5b between IBV 3575/08 and 2575 WT, we conjecture that these accessary proteins contribute to the blockade of PRR expressions, delayed immune response, and enhanced virulence of IBV 3575/08 in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a natural recombinant strain containing partial nsp regions from a low pathogenic H120 strain in the frame of a nephropathogenic strain possesses attenuated pathogenicity, which suggests strong associations between nsps and IBV virulence39. Studies on other coronaviruses such as MHV and severe acute respiratory syndrome coronavirus (SARS-CoV) have also shown that nsps are associated with viral replication and evasion of host innate immune response via viral RNA modification4041, host mRNA degradation, and IFN antagonist competition42. Therefore, given the low sequence homology in the accessory proteins 3a, 3b, and 5b between IBV 3575/08 and 2575 WT, we conjecture that these accessary proteins contribute to the blockade of PRR expressions, delayed immune response, and enhanced virulence of IBV 3575/08 in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Generation of 2=-O-MTase-deficient viruses has been used as a strategy to develop effective live attenuated vaccines (9)(10)(11)(12). Chemical and polypeptide inhibitors targeting viral 2=-O-MTase have been shown to function as antivirals (13)(14)(15).…”
Section: Methylation Of the 5=-cap Structure Of Viral Rnas Plays Impomentioning
confidence: 99%
“…Interestingly, the nsp10 residues involved in the nsp10/nsp16 interaction are quite conserved within the CoV family and it was recently demonstrated that nsp10 of different CoVs (FCoV, MHV, SARS-CoV, MERS-CoV) is functionally interchangeable in the stimulation of nsp16 2 0 -O-MTase activity . Thus, molecules or peptides blocking this interface may have broad-spectrum anti-CoV effects, a concept that was explored and supported using synthetic peptides that mimic the nsp10 interface and suppress nsp16 2 0 -O-MTase activity in vitro (Ke et al, 2012;Wang et al, 2015). The antiviral effect of the MHV TP29 peptide, for example, was first demonstrated in MHV-infected cells and was subsequently confirmed to limit MHV replication in mice and to enhance the type I interferon response .…”
Section: The Nsp16 2 0 -O-methyl Transferasementioning
confidence: 99%